Oclusopatias em crianças e adolescentes escolares no município de Feira de Santana, Bahia - Meira, Ana Cláudia Lima de Oliveira (2010)
Malocclusions rank third among public health dental problems and, in certain ages, they reach the second position. In Brazil they have a high prevalence. The objectives of the presente study were to investigate the epidemiologic profile of malocclusions in 12-year-old students, in the city of Feira de Santana, Bahia, in 2009, by assessing their prevalence; to describe the students’ socio-demographic characteristics; and to search for possible associations. The work was carried out by means of a population-based epidemiologic collection and the use of the DAI ( Dental Aesthetic Índex ) indicator. A total of 919 students were examined by a single examiner and noter ( trained and calibrated: initial Kappa=0.92 and during research=0.93 ). The students came from city, state, and private school systems in both rural and urban zones, and were selected through a complex ( by conglomerates ) sample, representative of Feira de Santana municipality. Descriptive measurement of frequency,bivaried analysis with quisquare (?) tests, and multivaried analysis, through the method of logistic regression, were used in order to assess possible associations. The findings showed that the prevalence of malocclusions among the examined students was high (53%), 10.1% being very severe/ disabling; 17.2% severe, and 25.7% defined. There was no significant difference between the necessity of treatment and the type of school ( private, city, or state ) ( p value=0.85 ); zone ( urban / rural ) ( p value=0.79 ); sex ( p value=0.45 ) ; race ( p value=0.21 ). Statistically significant associations were found between severe / disabling malocclusions and thumb / pacifier sucking, dental loss and visits to the dentist. Conclusion: The prevalence of malocclusions in the studied 12-year-old population, in the city of Feira de Santana, Bahia, showed high epidemiologic values, being more prevalent ( 46% higher ) among those students who had made use of pacifiers for longer than 36 months and those who had gone to the dentist in the last month ( 28% higher). The study made evident the necessity of giving greater attention to such a serious situation, so as to reduce the prevalence of the severe and disabling forms to low indices, compatible with the public service resources.